Monoculture Maize (Zea mays L.) Cropped Under Conventional Tillage, No-tillage and N Fertilization: (I) Three Year Yield Performances - Vincenzo Tabaglio; Carolina Gavazzi (Italian Journal of Agronomy)
A three-year (2004-2006) field trial was carried out to compare two agricultural land management systems, in the Po Valley (Northern Italy). Conventional tillage and No-tillage (hereafter indicated as CT and NT, respectively) were compared for maize treated with three levels of nitrogen. The soil was a fine-loamy, mixed, mesic Ultic Haplustalf, that had been under processing tomato in the previous year. Experimental design was a split-plot with four replicates, with the management system as the main factor and nitrogen fertilization (0, 250 and 300 kg N ha-1 year-1) as the secondary factor. Cumulative 3-yr yields of grain and total biomass of NT maize plants were 8% lower than those obtained under CT management, but not significantly different. No N starter was distributed in the first conversion year, causing 17% less grain yield in the NT plots compared with the CT plots. The N fertilizing with 250 and 300 kg N ha-1 year-1 determined statistically equal grain yields, demonstrating the waste of the extra 50 kg N at the N2 rate. Overall, the results for the three years indicate that on an Ultic Haplustalf conversion from a ploughed regime to mature NT conditions could be achieved over a relatively short period.